Electrical measurement, signal processing and displays. - Webster, John Goodwin, 1932- (Boca Raton : CRC, 2004)
Samenvatting:Electrical Measurement, Signal Processing, and Displays describes the useof instruments and techniques for practical measurement ofelectromagnetic variables, signal processing equipment and parameters,and various types of displays, from cathode ray tubes to LED devices. Forthis volume, chapters relevant to these topics were culled from thebestselling Measurement, Instrumentation, and Sensors Handbook andrevised by their original authors to bring them thoroughly up to date.This is a concise, well-illustrated, and highly practical reference. Itsets forth the principles, formulas, and equations engineers andscientists need for solving the instrumentation and measurement questionsthey encounter in practice, particularly when problems arise in areasoutside their own specialties.
Keywords: Meetinstrumenten; Metingen (elektrotechniek).